Enhancing Employee Performance: The Role of Work Discipline, Organizational Culture, and Competence in Shaping OCB at West Java Disaster Management Agency - Sumanti, Nur Alia; Erni Rusyani; Atty Tri Juniarti (Profesional Muda Cendekia Publishing, 2025)
Research Aims: This study aims to provide a factual description of the influence of work discipline, organizational culture, and competence on organizational citizenship behavior (OCB) and its impact on employee performance at Regional Disaster Management Agencies (BPBD) across West Java. Design/methodology/approach: This research employs a quantitative method with descriptive and verificative analysis. The analysis tool used is Structural Equation Modelling (SEM). The sample consists of 242 civil servants working at BPBDs across West Java. Research Findings: The findings reveal a significant influence of work discipline, organizational culture, and competence on OCB, with an impact magnitude of 70.22%. Other variables not examined account for 29.78%. Additionally, there is a significant influence of OCB on the performance of civil servants at BPBDs across West Java, with an impact magnitude of 80.51%, while other unexplored variables account for 19.49%. Theoretical Contribution/Originality: This study contributes to the understanding of how organizational factors such as work discipline, organizational culture, and competence shape OCB, which in turn significantly enhances employee performance, particularly in the context of public service institutions like BPBD.